Mobile application to digitize handwritten patient records in peruvian public hospitals (LACCEI, 2024)
This research has shown that public hospitals need a digitization model that allows the availability of medical records for patient medical consultation within a repository that unifies their medical information. This article presents MEDREC APP, a mobile application aimed at public hospitals of the Ministry of Health (MINSA), in order to expedite the immediate obtaining of the medical history in digital format, and to visualize their medical care. The main function of this solution is based on Optical Character Recognition (OCR) as a text extraction process by capturing images of handwritten medical history formats and registering them within the mobile application in digital format. As part of the validation process, indicators were defined, surveys and interviews were conducted with our users of the application: the medical staff. The results obtained show that the average time to obtain a medical history was reduced from an average of 25 to 20 minutes to 6 minutes, which means a reduction of 14 minutes, equivalent to approximately 70%.